Evaluation of the residual nitrite concentrations of locally produced and imported meat products in Kosovo - Rysha, A; Kastrati, GF; Jurkovic, J; Kabashi-Kastrati, E (Journal of the Hellenic Veterinary Medical Society, 2022)
The use of food additive nitrite as curing agents is common in meat products, but their concentration in these products has raised the interest of researchers, because of the possible toxicity to humans. The aim of this study is to assess the nitrite concentration in meat products, which are highly used by all population groups in Kosovo. A total of 44 different meat products samples available on sale to the population, were assessed for residual nitrite using the spectrophotometric method that uses absorption in visible part of spectra. The amount of residual nitrites was detected in 19 (43%) of the samples, which included beef and chicken sausages, chicken & beef salami as well as beef prosciutto samples. The nitrite residue ranged between 0.1 and 11.5 mg/kg and was below the limits on the concentration of nitrites in meat products established by EU regulation 601/2014. Although these findings show that, the nitrite residue in the analyzed meat products is within the permitted limits, the highest presence of residual nitrite in industrial and low-cost meat products indicates a need for further assessments of nitrite exposure among consumers.